The Effect of Leverage And Profitability on Earnings Management With Managerial Ownership As A Moderating Variable in Manufacturing Companies Listed on the Indonesia Stock Exchange In 2020-2023 - Faisal, Ahmad; Heniwati, Elok; Yantiana, Nella; Noviarty, Helisa; Rusmita, Sari (International Journal of Scientific Research and Management (IJSRM), 2024)
This study aims to analyze the effect of leverage and profitability on earnings management and test the role of managerial ownership as a moderating variable in the relationship in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for 2020-2023. The method used in this study is a quantitative approach with secondary data analyzed using SPSS version 25. The study's results indicate that leverage has a significant effect on earnings management and profitability, which also has a significant effect on earnings management. However, managerial ownership cannot moderate the effect of leverage on earnings management nor the effect of profitability on earnings management.